Implementación del sistema contable en el bazar papeleria Silva de la ciudad de Loja, en el periodo comprendido agosto – septiembre del 2016 - Trelles Guzmán, Narcisa de Jesús (2017)
The present thesis work arises first as a requirement to obtain the degree of Accounting and Auditing CPA. In addition it is proposed with the purpose of having a real appreciation of the financial situation of the business and thus be able to propose the appropriate solutions to the existing problem. For the development of the titling work, it was necessary to establish a general objective and the corresponding ones, for which it was necessary to collect source documentation to establish the initial state of the company; the Initial Inventory of all the goods, values and obligations that the commercial has been developed; documents, receipts and accounting and auxiliary records were designed to support the transactions carried out during the accounting period; financial statements were prepared that demonstrate the real economic and financial situation of the bazaar company. Finally, real and timely information was provided to the owner, based on the accounting and tax regulations, allowing it to comply with the requirements established by the control agencies, so it is recommended to continue with the accounting process applied, making use of technological tools for a more adequate control of the goods, therefore it is recommended its implementation that helps to efficiently organize the commercial and can grow in the market.